ANALISIS IMPLEMENTASI PERATURAN DAERAH TENTANG PENGELOLAAN DAN RETRIBUSI PELAYANAN PERSAMPAHAN KOTA BUKITTINGGI - Fitria Fatma; Yogi Krisma Warman (HUMAN CARE JOURNAL, 2023)
The waste problem in Indonesia is quite a national problem because it needs to be handled from upstream to downstream. In Indonesia's Waste Statistics, it was stated that of Indonesia's total population of 232.8 million people, the total waste generated was 38.5 million tons/year. The purpose of this study was to determine the analysis of regional regulation implementation number 5 of 2014 Bukittinggi concerning waste management and retribution for waste services in Bukittinggi 2022. This type of this study was a qualitative. By using purposive sampling method, 15 people were chosen as the partisipant for 4 weeks, the data was analyzed through input variables, process, and output. The results of this study found that the input input components (human resources, funds, facilities & infrastructure and policies) that the basis of the regional regulation policy No. 5 of 2014 concerning waste management, and waste retribution, for funds are sufficient, for human resources are sufficient, and infrastructure was not yet fully sufficient. Description of the process (effectiveness, efficiency, adequacy, alignment, responsiveness, accuracy and supervision) effectiveness had been running well and efficiently and adequacy was good as well as smoothing while for responsiveness all public complaints had been responded to quickly by the environmental service and are appropriate and have supervision was carried out. The result of regional regulation no 5 of 2014 there were still many people who did not understand waste management, there were still many people who did not sort organic and inorganic waste. In short, it can be concluded that the policy is implemented properly. It is expected that necessary to add human resources in waste management and waste service fees with environmental education background.